A contrastive study of linguistic features of proverbs expressing cause-effect in english and in vietnamese (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Proverb is regarded as one of the noblest genres of traditional culture, reflecting every aspect of the cultural social life, and an aspect of living language with many certain linguistic features. Therefore, studying and contrasting proverbs of different nations as well as applying the results of studying are practically useful for learning and teaching languages, helping learners master the target language and improve their communicative competence. In this thesis, I aim to investigate the similarities and differences of proverbs expressing cause-effect in English and Vietnamese, especially in terms of semantic and syntactic features. This is a qualitative and quantitative research based on descriptive and contrastive research methods. 250 samples in English and 250 Vietnamese ones are collected from different sources such as dictionaries, books, the Internet for the sake of the semantic and syntactic feature analysis. The findings of the thesis shows the remarkable differences between English and Vietnamese proverbs expressing cause-effect. In terms of syntactic features, there is a considerable differences in the frequency of sentence types used in English and Vietnamese and proverbs of cause-effect, especially in compound sentence (NE 27 # FE = 10.8% compared to NV = 185 # FV = 74%) due to the difference between English and Vietnamese. In terms of semantic features, the most significant differences between English and Vietnamese proverbs expressing cause-effect lie on the semantic fields of family & marriage relationship (NE = 21 # FE = 8.4% Vs NV = 34 # FV = 13.6%) and social relationship (NE = 38 # FE = 15.2% Vs NV = 52 # FV = 20.8%). The main reason could be due to the difference in cultural features between the two nations. The thesis also suggests some implications for the teaching and learning of proverbs in general, and those for the translating of proverbs expressing cause-effect from English into Vietnamese and vice versa in particular